About the nonlinear vibration equation of the beam - Khang, Nguyen Van; Huong, Nguyen Thi Van; Quyen, Nguyen Van; Chung, Pham Thanh (Vietnam Journal of Mechanics, 2023)
In this paper, we present the establishment the vibration equation for the study of nonlinear beam effects. A illustrative example allows us to derive equations und use nonlinear vibration for calculating vibration of beams.